ELTROMBOPAG THERAPHY IN CASES OF APLASTIC ANEMIA: A CASE REPORT - Gede Resha Wisadianta; Ngakan Ketut Wira Suastika (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2023)
Abstract: Eltrombopag Theraphy In Cases Of Aplastic Anemia: A Case Report. Management of cases of aplastic anemia is challenge. The definitive treatment is bone marrow transplantation, but it is expensive, the complication rate is high and the success rate is still low. Recent evidence shows that eltrombopag theraphy respods to thrombocytopenic conditions, and even other cytopenia. We report an 18 years old man with aplastic anemia with severe pancytopenia. The patient showed an inadequate response to theraphy with eltrombopag theraphy for three months of therapy.